What Have We Learned? : Macroeconomic Policy After the Crisis. (International Monetary Fund, 2014)
Since 2008, economic policymakers and researchers have occupied a brave new economic world. Previous consensuses have been upended, former assumptions have been cast into doubt, and new approaches have yet to stand the test of time. Policymakers have been forced to improvise and researchers to rethink basic theory. George Akerlof, Nobel Laureate and one of this volume's editors, compares the crisis to a cat stuck in a tree, afraid to move. In April 2013, the International Monetary Fund brought together leading economists and economic policymakers to discuss the slowly emerging contours of the macroeconomic future. This book offers their combined insights.